A filosofia e o filosofar como instrumentos para o saber pensar com autonomia - Ramalho, Ellen Maianne Santos Melo (2014)
His paper discusses the issue of the teaching of philosophy as a curriculum subject in the Brazilian high school, aiming to answer the following problem: How can a teaching of philosophy in enabling the development of the ability to think independently? To answer this question we used the methodology to bibliographic search - having as reference the main theorists John Dewey (1959 and 2010), Matthew Lipman, ( 992.1995 and 1990 ), Deleuze and Guattari (1992 and 2006) - and field research. Thus we present a discussion on the reintegration of philosophy as a compulsory subject in high school curriculum, questioning their contributions to education and identify what teaching of philosophy could develop intellectual autonomy of learners. The main contribution that philosophy has to give education is to assist in the development of intellectual autonomy of the learner. We believe that intellectual autonomy is the cognitive ability of the student can develop which makes it a critical and creative agent in the construction of their own knowledge. It is the philosophical teaching of philosophy, one that can work through the philosophy through philosophizin, which can assist students in developing their intellectual autonomy, provide for the development of thinking skills that help in the formation of critical and creative subjects.